PENGARUH FISIOTERAPI DADA DALAM UPAYA PENINGKATAN PENGELUARAN SPUTUM PADA PASIEN TUBERKOLOSIS PARU DI RUMAH SAKIT IMELDA PEKERJA INDONESIA MEDAN TAHUN 2021 - Aditia Mulia Ningrum; Rostinah Manurung; Christina Magdalena T.Bolon; Paskah Rina Situmorang (Jurnal Ilmiah Keperawatan IMELDA, 2022)
Pulmonary tuberculosis (pulmonary TB) is a disease that has long been known and is still a health problem in various countries in the world. Transmission of this disease through the intermediary of saliva or phlegm (sputum) of patients containing pulmonary tuberculosis bacilli. This research was conducted at Imelda Indonesian Workers General Hospital in Medan. The research method used in this study is a correlation research method using a cross-sectional design. The sample of this research is 34 respondents with non-probability type by using purposive sampling technique. The purpose of this study was to see or determine whether or not there is a relationship between chest physiotherapy and increased sputum production. The results showed that the P-value was 0.19 where p-value <0.05, which means that there is an influence between physiotherapy and increased sputum production in pulmonary TB patients at the Imelda General Hospital for Indonesian Workers. It is suggested that the results of this study are expected as information for lecturers and students to better understand the relationship between chest physiotherapy and increased sputum production in patients with pulmonary TB and to motivate students to learn more about the relationship between chest physiotherapy and increased sputum production so that they can prepare themselves. facing the practice of the nurse profession in providing nursing care about pulmonary tuberculosis (pulmonary TB) both at home and in the community.